Mediterranean diet and risk of breast cancer: An umbrella review - González-Palacios Torres, Carla; Barrios-Rodríguez, Rocío; Muñoz-Bravo, Carlos; Toledo, Estefanía; Dierssen, Trinidad; Jiménez-Moleón, José Juan (Elsevier, 2023)
Background The Mediterranean Diet (MedDiet) is a healthy dietary pattern which has been related to a lower risk of certain chronic diseases, such as some cancers. However, its role in breast cancer development remains unclear. This umbrella review aims to summarize the highest available evidence on MedDiet and breast cancer risk. Methods Pubmed, Web of Science, and Scopus electronic platforms were searched for relevant systematic reviews and meta-analyses. The selection criteria included systematic reviews with or without meta-analysis including women aged 18 years or older which evaluated the adherence to a MedDiet as the exposure and incidence of breast cancer as the outcome variable. Overlapping and quality of the reviews using AMSTAR-2 tool were independently assessed by two authors. Results Five systematic reviews and six systematic reviews with meta-analysis were included. Overall, 4 systematic reviews – two with and two without meta-analysis – were rated as of high quality. An inverse association was found in 5 of the 9 reviews which evaluated the role of MedDiet on the risk of total breast cancer. The meta-analyses showed moderate-high heterogeneity. The risk reduction seemed to be more consistent among postmenopausal women. No association was found for MedDiet among premenopausal women. Conclusions The results of this umbrella review suggest that adherence to a MedDiet pattern had a protective effect on the risk of breast cancer, especially for postmenopausal breast cancer. The stratification of breast cancer cases and conducting high-quality reviews are aspects needed to overcome the current results’ heterogeneity and to improve knowledge in this field.
Keywords: Mamas-Cáncer-Prevención; Hábitos alimenticios; Dieta; Nutrición; Dieta en enfermedades; Breast cancer; Mediterranean diet; Umbrella review